Analisis Lingkungan Sekolah Dan Media Pembelajaran Terhadap Motivasi Belajar Siswa Kelas Xi Ips Man 1 Surakarta Tahun Ajaran 2016/2017 - Nur Baistih, Larasita; , Drs. Sudarto, HS. MM (2017)
ABSTRACT The purpose of this research is to understand the contribution of the school environment and the medium of learning toward students learning motivation of grade eleven of social science program at MAN 1 Surakarta academic year 2016/2017 either persial and simultan. Type of the research is quantitative associative. The population of this research is students of grade eleven of social science program in MAN 1 Surakarta academic year 2016/2017 that amounts to 157 students with samples 110 students taken with the fusion between the random sampling. The technique of collecting data is using a inquiries method which has been tested with validity test and reliability test. Technical data analysis used in this reseach are double regression, the test t, the test F, effective donations and relatively donations. The conclusions of this reseach are: 1) there is significant influence between the school environment toward the learning motivation based on the t test which result in t_hitung>t_tabel, namely 5,211 > 1,65882 and the value of significant < 0.05, namely 0,000. 2) there is significant influence between the medium of learning toward learning motivation based on the t test which result in t_hitung>t_tabel, namely 9,244 > 1,65882 and the value of significant < 0,05, namely 0,000. 3) there is significant influence between the school environment and the medium of learning motivation to learn based on the F test which result in F_hitung>F_tabel, 13,634 > 3,08 with the value of significant 5%. The results of reckoning for R^2 value are 23,1% of learning motivation influenced by environmental school and medium of learning, and the remains value are 76,9% influenced by other variable that not is scrutinized in the study. Key words: learning motivation, school environment, medium of learning.